2020
DOI: 10.21521/mw.6415
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bisphenol A on spermatological parameters of New Zealand White Rabbits

Abstract: This study aimed to investigate the possible reproductive toxicity dose of bisphenol A (BPA) in male New Zealand white rabbits. Prior to the experiment, male rabbits (n = 24) were acclimatized to laboratory conditions and trained for semen collection for 14 days. After the training period, rabbits were divided into 4 groups of 6: positive controls and 3 different doses of BPA (10, 20 and 100 mg/kg/day). All treatments were administered by oral gavages for 9 weeks following the training period. At the end o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…There are strong pieces of evidence that BPA can negatively alter testosterone production, sperm count, sperm motility, and overall spermatogenesis and sperm quality in a man and different mammals (11,18,35). Moreover, the results from our laboratory suggested as low as 10 mg/kg/d dose of oral BPA had negative effects on serum testosterone, progressive motility, and spermatozoa concentration in New Zealand White rabbits by changing the oxidant-antioxidant status of the testicular tissues (16). Recently, it has been reported that, due to its high antioxidant capacity, 2 mg/kg/day punicalagin had a positive effect on antioxidant activity in testicular tissues and increased sperm count in New Zealand rabbits (34).…”
mentioning
confidence: 74%
See 3 more Smart Citations
“…There are strong pieces of evidence that BPA can negatively alter testosterone production, sperm count, sperm motility, and overall spermatogenesis and sperm quality in a man and different mammals (11,18,35). Moreover, the results from our laboratory suggested as low as 10 mg/kg/d dose of oral BPA had negative effects on serum testosterone, progressive motility, and spermatozoa concentration in New Zealand White rabbits by changing the oxidant-antioxidant status of the testicular tissues (16). Recently, it has been reported that, due to its high antioxidant capacity, 2 mg/kg/day punicalagin had a positive effect on antioxidant activity in testicular tissues and increased sperm count in New Zealand rabbits (34).…”
mentioning
confidence: 74%
“…Similarly, in the current study, BPA did not show a significant effect on serum inhibin, FSH, and LH levels. Although changes in reproductive hormones in mammals can be perceived as a warning that there may be reproductive toxicity, it should be taken into consideration that even if these hormones are in their normal blood concentrations, there may be damage to the testicular tissue due to oxidative stress and this can lead to adverse effects on spermatogenesis (16,23).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is thought that the intensive use of BPA resulted in environmental pollution that could adversely affect human and animal health, and lead to an increase in oxidative stress in the body (Hamed and Abdel-Tawwab 2017). BPA is closely associated with oxidative stress in different tissues and organs, and further cause a number of metabolic problems (Ogo et al 2017, Karabulut 2019, Karabulut and Gulay 2020. Today, reducing the use of BPA and other external oxidative stress sources is extensively discussed elsewhere (ECHA, 2021).…”
Section: Introductionmentioning
confidence: 99%